Предмет: Алгебра,
автор: OCULUSIII
(x-7)^2 - (x-5)(x+6) = 4
Запиши число в поле ответа.
________________________
Ответы
Автор ответа:
2
Ответ:
5
Объяснение:
(x-7)^2 - (x-5)(x+6) = 4
х² -14х+49-(х²+6х-5х-30)=4
х² -14х+49-(х²+х-30)=4
х² -14х+49-х²-х+30=4
79-15х=4
-15х=4-79
-15х= -75
х= -75 : (-15)
х= 5
Похожие вопросы
Предмет: Английский язык,
автор: Melnikyaroslav
Предмет: Английский язык,
автор: Братело
Предмет: Английский язык,
автор: Аноним
Предмет: Литература,
автор: elizavetazubov2009
Предмет: Алгебра,
автор: toltoev90